Match making: Using data-matching to find people missing out on government assistance - Baker, D (The Australia Institute, 2012)
One of the tools used by the government in pursuit of ‘welfare cheats’ is data-matching. The Data-matching Program cross-checks income and personal details held by one agency against similar data held by other agencies, primarily the Australian Taxation Office. The focus of this program is identifying overpayments amongst existing welfare assistance recipients (the difference between overpayment and fraud is not often explained in public reporting of ‘welfare cheating’). However, this focus results in neglect of those people who may be eligible for assistance but are not receiving it. This paper considers how data-matching could also be used to improve the delivery of social security assistance payments rather than simply as a revenue raising exercise.
Policy Brief No. 34
Keywords: Benefits and Payments; Income, wealth and finances; Benefits and Payments; Income, wealth and finances